The focus on sample quality: Influence of colon tissue collection on reliability of qPCR data - Korenkova, Vlasta; Slyskova, Jana; Novosadova, Vendula; Pizzamiglio, Sara; Langerova, Lucie; Bjorkman, Jens; Vycital, Ondrej; Liska, Vaclav; Levy, Miroslav; Veskrna, Karel; Vodicka, Pavel; Vodickova, Ludmila; et al. (Scientific reports, 2016)
Successful molecular analyses of human solid tissues require intact biological material with well-preserved nucleic acids, proteins, and other cell structures. Pre-analytical handling, comprising of the collection of material at the operating theatre, is among the first critical steps that influence sample quality. The aim of this study was to compare the experimental outcomes obtained from samples collected and stored by the conventional means of snap freezing and by PAXgene Tissue System (Qiagen). These approaches were evaluated by measuring rRNA and mRNA integrity of the samples (RNA Quality Indicator and Differential Amplification Method) and by gene expression profiling. The collection procedures of the biological material were implemented in two hospitals during colon cancer surgery in order to identify the impact of the collection method on the experimental outcome. Our study shows that the pre-analytical sample handling has a significant effect on the quality of RNA and on the variability of qPCR data. PAXgene collection mode proved to be more easily implemented in the operating room and moreover the quality of RNA obtained from human colon tissues by this method is superior to the one obtained by snap freezing.
Keywords: nádorové proteiny; Gene Expression Regulation, Neoplastic; kolon; Quality Control; řízení kvality; kvantitativní polymerázová řetězová reakce; DNA-topoisomerasy I; Cryopreservation; Nitrogen; RNA, Ribosomal, 18S; regulace genové exprese u nádorů; DNA nádorová; ribozomální DNA; odběr biologického vzorku; stanovení celkové genové exprese; Organ Preservation Solutions; reprodukovatelnost výsledků; Real-Time Polymerase Chain Reaction; Preservation, Biological; Reproducibility of Results; DNA, Neoplasm; Gene Expression Profiling; DNA Topoisomerases, Type I; rychlé screeningové testy; RNA nádorová; lidé; Carcinoma; roztoky pro uchovávání orgánů; Humans; Colon; High-Throughput Screening Assays; Specimen Handling; dusík; karcinom; fixace tkání; Colonic Neoplasms; Neoplasm Proteins; Tissue Fixation; nádory tračníku; DNA, Ribosomal; RNA ribozomální 18S; kryoprezervace; RNA, Neoplasm; ochrana biologická